A Case Study of Severe Esophageal Dysmotility following Laparoscopic Sleeve Gastrectomy - Caroline E. Sheppard; Daniel C. Sadowski; Richdeep Gill; Daniel W. Birch (Case Reports in Surgery)
Following bariatric surgery, a proportion of patients have been observed to experience reflux, dysphagia, and/or odynophagia. The etiology of this constellation of symptoms has not been systematically studied to date. This case describes a 36-year-old female with severe esophageal dysmotility following LSG. Many treatments had been used over a course of 3 years, and while calcium channel blockers reversed the esophageal dysmotility seen on manometry, significant symptoms of dysphagia persisted. Subsequently, the patient underwent a gastric bypass, which seemed to partially relieve her symptoms. Her dysphagia was no longer considered to be associated with a structural cause but attributed to a “sleeve dysmotility syndrome.” Considering the difficulties with managing sleeve dysmotility syndrome, it is reasonable to consider the need for preoperative testing. The question is whether motility studies should be required for all patients planning to undergo a LSG to rule out preexisting esophageal dysmotility and whether conversion to gastric bypass is the preferred method for managing esophageal dysmotility after LSG.